Developing High School Students' Creativity Through Practical Work on Utilizing Durian Peel Waste in Project-Based Learning - Siti Marfu'ah; Ratna Farwati; Annisa Meristin (Chemistry Education Department of Education and Teaching Faculty, 2024)
This study aims to develop a practical work design for creating briquettes from durian peel waste and to identify the development of high school students' creativity through this practical work in the context of project-based learning on petroleum. Adopting a mixed-methods approach, this research involved 48 eleventh-grade students from a high school in South Sumatra. The practical work design encompassed six critical stages: raw material preparation, carbonization, pulverization, mixing, molding, and drying durian peel waste into briquettes. The research comprehensively assessed students' creativity across three dimensions: creative thinking skills, creative attitudes, and creative actions. The results demonstrated significant improvements: creative thinking skills showed an n-gain of 0.59, creative attitudes an n-gain of 0.68, and creative actions an impressive n-gain of 0.84. This approach facilitates a deeper understanding of chemical concepts and aligns with the Merdeka Curriculum's principles of developing 21st-century skills. By integrating contextual learning, environmental awareness, and practical innovation, the study provides a meaningful approach to chemistry education that encourages student creativity, problem-solving, and entrepreneurial thinking while addressing waste management and alternative energy challenges. The research implications underscore the importance of implementing project-based, contextually relevant learning strategies in high school chemistry education to enhance student engagement and skill development.